Celiakija - Brecelj, Jernej (Medicinski razgledi, 2010)
Celiac disease is a system ic disease with autoimmune inflammatory response triggered by gluten in genetically susceptible individuals. It is more prevalent than previously thought and may appear at any age. Apart from typical presentation with malabsorption in infants and toddlers it might present with many atypical symptoms and signs. It is diagnosed by sensitive and specific blood tests and typical histological changes of duodenal mucosa. The treatment is still strict gluten free diet but novel therapies are being tested. In this article celiac disease is being reviewed according to new guidelines for children. We also included a short case presentation for illustration.
Keywords: celiakija; diagnostika; sistemske bolezni; therapy; zdravljenje